1981
DOI: 10.1002/kin.550131204
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of reactions between aromatic olefins and hydroxyl radicals

Abstract: The rates of the reactions of hydroxyl radicals (OH) with styrene, a-methylstyrene, and P-methylstyrene have been measured by irradiating mixtures of these aromatic olefins and NO in an environmental chamber a t 298 K. Experimental conditions were used whereby the competition of ozone with OH in oxidizing the hydrocarbons could be considered negligible.The rate constant values, obtained by a relative method using isooctane as reference hydrocarbon, are: styrene (5.3 f 0.5) X lo-" cm3/molec.s, a-methylstyrene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
6
26
1
Order By: Relevance
“…The available data on the OH reaction with some of these species indicate that this process is quite fast, the rate coefficients being k OH = (5-7.8) × 10 −11 cm 3 molecule −1 s −1 [8][9][10]. Therefore, in order to evaluate the atmospheric importance of other loss processes (photolysis and ozonolysis) we have measured their UV absorption cross-sections and the rate coefficients for their ozonolysis.…”
Section: E-mail Address: Mellouki@cnrs-orleansfr (A Mellouki)mentioning
confidence: 99%
See 1 more Smart Citation
“…The available data on the OH reaction with some of these species indicate that this process is quite fast, the rate coefficients being k OH = (5-7.8) × 10 −11 cm 3 molecule −1 s −1 [8][9][10]. Therefore, in order to evaluate the atmospheric importance of other loss processes (photolysis and ozonolysis) we have measured their UV absorption cross-sections and the rate coefficients for their ozonolysis.…”
Section: E-mail Address: Mellouki@cnrs-orleansfr (A Mellouki)mentioning
confidence: 99%
“…The rate coefficients values used for the calculations are (in cm 3 molecule −1 s −1 ) (5.8 ± 0.1) × 10 −11 [10], (5.3 ± 0.6) × 10 −11 [9] and (7.8 ± 0.3) × 10 −11 [8] for the reactions of OH with styrene, ␣-methylstyrene and indene, respectively. They are (1.51 ± 0.04) × 10 −12 [10] and (4.08 ± 0.26) × 10 −12 [8] for the reactions of NO 3 with styrene and indene, respectively.…”
Section: Atmospheric Implicationsmentioning
confidence: 99%
“…Although both acetophenone and benzeneacetaldehyde may also be formed from other precursors (see e.g. Bignozzi et al, 1981), ethylbenzene is probably the predominant chemical source due to its high abundance. If contributions of other precursors are neglected, the variations of the mixing ratios of ethylbenzene ([EB]), acetophenone ([AP]), and benzeneacetaldehyde ([BA]) can be described by…”
Section: Sequential Reaction Model and Photochemical Agementioning
confidence: 99%
“…For example, Sloane and Brudzynski (1979) reported that OH would most likely attack both the ring and side chain of styrene, but Bignozzi et al (1981) noted that only the styrene side chain was more susceptible to OH oxidation. In these studies, the rate constant of the initial reaction was measured to be at the magnitude of 10 À11 cm 3 molecule À1 s À1 , suggesting that the initial reaction of OH with styrene could occur quite easily, and the effect of this oxidation reaction on the atmosphere should not be ignored (Atkinson and Aschmann, 1988;Bignozzi et al, 1981). However, up to date, no experimental and theoretical investigations were conducted to probe the SOA formation possibility from these atmospheric reactions.…”
Section: Introductionmentioning
confidence: 97%
“…The styrene-OH oxidation reaction has been investigated in previous experiments (Atkinson and Aschmann, 1988;Bignozzi et al, 1981;Sloane and Brudzynski, 1979), but these studies only focused on identifying the atom of styrene which is most likely to be attacked by OH and thus predicting the easiest initial reaction in the atmosphere. For example, Sloane and Brudzynski (1979) reported that OH would most likely attack both the ring and side chain of styrene, but Bignozzi et al (1981) noted that only the styrene side chain was more susceptible to OH oxidation.…”
Section: Introductionmentioning
confidence: 99%